Hydrological modelling of river basin in agriculture area by using soil and water assessment tool - JALGAONKAR, B. R. (Journal of Soil and Water Conservation, 2021)
The study based on hydrological modelling of river basin in agriculture area by using Soil and Water Assessment Tool (SWAT). This tool is basically a river basin scale model incorporating hydrological section namely catchment area, crop development, climate data store, characteristics of soil and water quality standards etc. It is escalating the working power and less spending time to keeping up the measuring station data, atmospheric changes on water and soil data globally. The study discusses the use of SWAT model and demonstrates hydrological operation in the west Banas river basin. In addition, the study also highlights the Sequential Uncertainty Fitting (SUFI-2) technique and three measurable parameters i.e. Coefficient of determination (R2), Nash-Sutcliff Effectiveness (NSE) and percent Bias (PBIAS). The study concludes that SWAT model performs accurately in calibration process and simulates hydrology within the west Banas river basin satisfactorily.